Menuju Gereja Pasca-Pandemi yang Inkarnasional, Relasional, dan Misional: Eklesiologi Dietrich Bonhoeffer dalam Dialog dengan Konsep Faithful Presence dari James Davison Hunter - Sartika, Meitha (Veritas : Jurnal Teologi dan Pelayanan, 2023)
The COVID-19 pandemic has become a major event that affects many aspects of life, including church life. The church needs to adapt itself to the changes that occur while responding to various situations around it. This situation brings two questions for the church to reflect on, namely whether the church has been paying attention to the concrete issues around it and whether the church has truly been present for others. This paper aims to show that the post-pandemic church needs to be a church that is faithfully present for others. For that, I will discuss the impact of the pandemic on the church. Then, I will explore Dietrich Bonhoeffer’s view of the church for others and James Davison Hunter’s ideas about faithful presence. Both of them are trying to show a church that wants to be present in the midst of society with various dynamics of life. Finally, I discuss these two views to construct an incarnational, relational, and missional post-pandemic ecclesiology.